Technical Debt: A Clean Architecture Implementation - Beltrão, Alessandro Caetano; Farzat, Fábio de Almeida; Travassos, Guilherme Horta (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e Prática, 2020)
Technical Debt (TD) and Technical Debt Management (TDM) are terms that are receiving increasing attention from practitioners and researchers. They reflect a concern on how shortcuts taken during the software development process can incur negative impacts on software maintainability and how practitioners may use tools and techniques to mitigate the effects of the debt over time. A widely used tool to manage TD on an implementation level is SonarQube with the SQALE method, as it allows developers and managers to track debt over time. However, even SonarQube has its weaknesses since it only provides a set of architecture agnostic rules for TD, and the implementation of new rules can prove to be a challenging job. In this paper, we discuss how, during a real industrial project on a Brazilian software house, we developed a set of rules based on the Clean Architecture model, created a plug-in for SonarQube, and integrated it into our development cycle. At last, the preliminary results show that using a rigorous set of rules allows keeping track of TD on an implementation level.